LIQUIDITY RISK, INCOME DIVERSIFICATION, AND BANK FINANCIAL PERFORMANCE - Rasyid, Rosmita; Bangun, Nurainun (Graduate Program of Universitas Tarumanagara, 2023)
Banking industry must have healthy financial performance in order to function properly as an intermediary organization between those who have capital and those who need it. Intense competition between banks, the emergence of the covid-19 pandemic and declining bank profits have forced banks to be more careful in managing risks and diversifying their income. This study aims to see the effect of liquidity risk and income diversification on banking financial performance. The research data comes from 36 listed companies on the Indonesian Stock Exchange (IDX) or with 108 observations of banking companies for the period 2019 - 2021. The dependent variable of this study is financial performance proxied by ROA (Return-on-Assets). Liquidity risk and income diversification are dependent variables. LDR (Loan-to-Deposit Ratio) is used to measure liquidity risk. Three ratios namely NII (Non- Interest-Income/Gross-Revenue-ratio), NII1 (Fee & Commission-Income/Revenue-ratio) and NIITA (Non-Interest-Income/Total-Assets-ratio) are used to measured income diversification. This study uses multiple regression analysis of panel data. The results of the study show that liquidity risk has a positive effect on bank financial performance. NII1 (Fee & Commission-Income/Revenue-ratio) has significant positive results on financial performance while the NII (Non-Interest-Income/Gross-Revenue-ratio) and NIITA (Non-Interest-Income/Total-Assets-ratio) do not have effect on financial performance of the bank.